Are patterns of vacant lots random? Evidence from empirical spatiotemporal analysis in Chiba prefecture, east of Tokyo. (March 2022) - Usui, Hiroyuki; Perez, Joan
According to the Japanese government, vacant lots are randomly generated and accumulated (without being rebuilt after demolition) in the process of increasing vacant lots, a phenomenon called urban perforation. Urban perforation in urban areas may trigger a high degree of inefficiency in public infrastructure management. However, this observation lacks theoretical and empirical foundations, a lacuna to which this paper will focus on. Consequently, our research objectives are to confirm: (1) whether or not vacant lots are randomly generated and (2) whether or not vacant lots are randomly accumulated as a result of random generation. The methodology includes a consistent and bottom-up approach to delineate urban areas (alongside statistical spatial analysis). Through theoretical and empirical analyses in Chiba Prefecture (situated in the eastern part of the Tokyo metropolitan region), we find that the random generation of vacant lots does not tend to continue in the same urban areas. Rather, in most urban areas, this process is a temporary phenomenon. Subsequently, phase transition generally shifts from random to clustered generation or vice versa. Nevertheless, once vacant lots are randomly accumulated in an urban area, this process tends to continue. The contributions of this article are not only to provide important spatiotemporal findings regarding the generation and accumulation patterns of vacant lots, but also to discuss how to apply policy for urban perforation where phenomena are significantly pronounced.